La ville et les enfants dans un processus éducatif - Irène Micha (Belgeo)
Urban studies can play a vital role in the educational process by highlighting multiple aspects of children’s socialization which shape also their spatial identities. The discussion in this article is based on a particular collaboration between primary and higher education in Greece, in the framework of projects focusing on the neighbourhoods of three primary schools and aiming at establishing a fruitful dialogue between pupils and university students. The bridge between two teaching practices led us to consider children as social actors and producers of knowledge; to examine their everyday space/s in a framework of local/global dialectics, seeking to identify the socio-spatial traces of memory, children’s flows and networks, and especially to mention the importance of their urban perception. This article is part of a continuing effort to develop alternative approaches drawing from children's processes of urban learning, which contribute to create fissures in several theoretical certainties about the city/Athens and particular areas in it.